2010
DOI: 10.1021/ja9087049
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Induced Cleavage of Carbon−Carbon Bonds: Bridge Rupture Reactions of Group 8 Dicarba[2]metallocenophanes

Abstract: Thermal treatment of dicarba[2]ferrocenophanes [Fe(eta(5)-C(5)H(4))(2)(CMe(2))(2)] (1), rac-[Fe(eta(5)-C(5)H(4))(2)(CHiPr)(2)] (rac-5), and meso-[Fe(eta(5)-C(5)H(4))(2)(CHtBu)(2)] (meso-7) at 240-300 degrees C in the melt led to cleavage of the carbon-carbon bond in the bridge. Compounds 1 and rac-5 underwent intramolecular abstraction of H* and yielded ring-opened, vinyl-substituted 1,1'-metallocenes, while meso-7 thermally converted to the more thermodynamically stable rac isomer. The corresponding dicarba[2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 83 publications
2
34
0
Order By: Relevance
“…Electron correlation effects were considered by using DFT methods that have evolved as a practical and effective computational tool, especially for organometallic compounds [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Thus, two DFT methods were used in this study.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Electron correlation effects were considered by using DFT methods that have evolved as a practical and effective computational tool, especially for organometallic compounds [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Thus, two DFT methods were used in this study.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…NaCp) which do not attack at Si [15]. Furthermore, as discussed in the previous section, cleavage of the bridge EeE bond has been demonstrated for a variety of [2]metallocenophanes [1f, 16,17,22], Until recently, the reactivity modes of [n]metallocenophanes were confined to these aforementioned bond-cleavage processes, with the concomitant release of molecular ring-strain. However, in a recent report a new mode of [n]metallocenophane reactivity based on metalemetal bond formation was elucidated.…”
Section: Metalemetal Bond Formation By Strained Ruthenocenophanesmentioning
confidence: 98%
“…In 2010, the results of a detailed investigation into the thermal reactivity of a series of dicarba[2]ferrocenophanes 10 e rac-14 (Schemes 3 and 4) were reported [16]. Rather than undergoing ROP, tetramethyl-substituted 11 afforded ring-opened, vinyl-substituted metallocene 12 under thermolysis conditions (240 C) (Scheme 3).…”
Section: Bridge Cleavage Reactions With Strained [2]ferrocenophanesmentioning
confidence: 99%
“…Computational studies on this system have confirmed the relative thermodynamic preference for the rac isomer over the meso form, a property reflected in the experimentally determined relative C−C bond lengths of the meso (1.612(3) Å) and rac isomers (1.565(7) Å). 84 The differences in observed reactivity for these species were rationalized through the presence or absence of hydrogen at the α position relative to the carbon atoms in the bridge. Thus, in species 35, an α-hydrogen facilitates H • abstraction and radical disproportionation to afford the ferrocene derivative 53.…”
Section: Recent Work On Strained [2]ferrocenophanesmentioning
confidence: 99%